HUBUNGAN PENDIDIKAN DENGAN POLITIK DALAM PERSPEKTIF HISTORIS - Huda, Mitakul (Jurnal An-Nahdhah, 2014)
The politics and education are not likely to be separated. Both are have close links associated with each other. The Politics that is not surrounded by education will destroy itself. Therefore , the politic always still needs education for the achievement of the political. And the education also requires political for the achievement of the educational goals. . Its just, which education and how education are supporting the politics that can be a good politics, and the otherwise, which political and how political can make the education be come into a good education. The point of a lot, the politics would be a good politics depends on the offenders good politics and the otherwise.